Theoretical Courses and Architectural Education: Studio-based Approach for Technical Writing Course (International Journal of Built Environment and Sustainability, 2024)
Technical writing skills are critical to ensure the success and integration of architecture and urban projects. The practice of architecture requires high communication skills to deliver ideas and plans to the different stakeholders in architecture projects. Clear technical communication provides mutual understanding of the aspects and requirements of projects to all involved parties including contactors, engineers, clients and even authorities, mitigating the high risks of misunderstandings. Technical writing allows for clear project documentation, facilitating coordination between interdisciplinary teams and improving decision making and problem solving. Architectural education relies mainly on hands-on experiences and design-oriented studios. Theoretical courses present a challenge for both architecture students and lecturers, as they are often taught in a lecture setting, which is not so familiar to architecture students, making them overwhelming to students. Theoretical courses challenge students as they often miss the link between concepts and application. Technical writing courses are hardly linked to students’ interests. This study presents a pedagogical approach to the course of Technical Writing in the Sustainable Architecture and Urban Design Program at Helwan University in Egypt. It presents an studio-based interactive approach through using in-class discussions, workshops, games, peer discussions and interactions. It also links sustainable architecture and urban design applications into students’ work, to ensure their interest in the course and their compound benefit. The paper presents the results of a tailor-made evaluation questionnaire to identify the most effective methods used in teaching the course, in addition to students’ key takeaways from the course. Results show that students learned the most of report writing and presentation skills, perceived the course as highly interactive and highlighted that using games enhanced their learning experience.
Keywords: Sustainable Architecture, Sustainable Urban Design, Technical Writing, Architecture Education, Interactive Learning, Sustainable Development